The pitfalls in entrepreneurship and small business research: A holistic view - Minai, Mohd Sobri; Uddin, Md Mohan; Ibrahim, Yusnidah (Canadian Center of Science and Education, 2014)
The academic and practical interest in the field of small business and entrepreneurship has recently gained considerable attention. However, an important area of concern within this field has been to find appropriate and suitable research approach or technique that could assist the researchers to produce positive research outcomes.Many researches in this field have been conducted without paying attention to some of their unique characteristics.Therefore, this study identifies and documents various pitfalls associated with these types of researches.It also offers the guidelines and important considerations for researchers in this area with the intention of reducing future weaknesses.